THE ROLE OF TRADITIONAL, SOCIAL, RELIGIOUS, AND GOVERNMENT LEADERS IN BUILDING HARMONIOUS RELATIONS BETWEEN RELIGIOUS PEOPLE IN JAYAPURA CITY - Amirullah Amirullah; Musa Rumbaru; Rahmawansyah Sahib (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
This study aims to explore and identify the role of the four pillars in building harmonious relations between religious groups in Jayapura-Papua City. The four pillars referred to here are traditional leaders, community leaders, religious leaders, and the government. This qualitative research is in the form of a case study. Data collection techniques through observation, interviews, and documentation. The results showed the synergy of the role of the four pillars in building harmonious relations between religious groups in Jayapura City through two fundamental processes. First, as a communicator through mediation communication strategies and media tools. The second is as a coordinator to overcome conflict tensions and continuity in coordination and coordination that is dynamic. The theoretical implications of this study show that synergy is needed for the role of traditional leaders, community leaders, religious leaders, and the government in realizing harmony between religious people. The limitations of this study have not examined the constraints, obstacles, or challenges of the synergy of the role of the four pillars in realizing harmonious relations between religious people in Jayapura City-Papua.